Effect of fatigue on reaction time, response time, performance time, and kick impact in taekwondo roundhouse kick - Sant`Ana, J.; Franchini, E.; da Silva, V.; Diefenthaeler, F. (Sports Biomechanics, 2017)
Reaction time and response time are considered important abilities and can potentially affect combat performance. This study investigated the effect of a specific fatigue protocol on reaction time, response time, performance time, and kick impact. Seven male athletes reported to the laboratory on two different days. During day one, athletes performed a specific progressive taekwondo test, and on day two, a protocol for determining reaction time, response time, performance time, and kick impact before and after a time to exhaustion test at an intensity level corresponding to the maximal kick frequency obtained during the specific progressive taekwondo test. Muscle activation from rectus femoris and kick impact of the preferred limb were assessed. No differences were observed for response time and performance time. However, kick impact decreased (43 ± 27 to 13 ± 10 g, p < 0.01) while reaction time increased (145 ± 51 to 223 ± 133 ms, p < 0.05). Moderate correlation was observed between kick impact and response time (r = 0.565; p < 0.01), and kick impact and performance time (r = 0.494; p < 0.05). Results indicate that coaches and athletes may use taekwondo training programmes on coordination-based exercises leading to improve response time and to reduce fatigue effects in order to improve technique effectiveness and enhance the possibilities of scoring in a competitive situation. ABSTRACT FROM AUTHOR